DYNAMIC CAPABILITIES IN THE CREATIVE ARTS INDUSTRY - Kanita, Ghia Ghaida; Respati, Resa (JURNAL ILMU MANAJEMEN DAN BISNIS, 2019)
Abstract. Â Dynamic ability is a form of knowledge that can create values for the company both with the results of innovation and transformation from input to output in order to produce sustainable competitive advantage. The purpose of this research is to know about what factors influence dynamic capabilities of a company or organization. In this study, more than that, what affects the dynamic capabilities in industries in Bandung. Creative industry is a collection of information related to information and information. Creative industry is an economic activity that produces added value from the art side. The creative arts industry is already boooming in Indonesia. Therefore, the author wants to learn about the dynamic capabilities that exist in the creative arts industry in Bandung. Things to look for are components such as environmental sensing capabilities, change capabilities and upgrades, technological flexibility capabilities, and organizational flexibility. Putri Pamayang Dance Studio is a dance studio in Bandung. This study uses a research-based design or Design Based Research (DBR). Based on the results of the study, the steps adopted by the Putri Pamayang Dance Studio are related to variation strategies, market testing strategies, development and development, backward integration, horizontal integration.Keywords. dynamic capabilities, sustainable competitive, environmental sensing capabilities, change and renewal capabilities, flexibility technology capabilities, and organizational flexibility.